Silicon crumble. (Economist, 2017)
The article discusses the impact of artificial intelligence (AI) on the semiconductor industry. Topics include the sales of graphics processing units (GPUs) chips for AI operations by the firm Nvidia Corp., changes to the market for traditional semiconductor firm Intel Corp., and the increasing amount of processing done through data centres rather than central processing units (CPUs) such as those made by Intel.